METODE INDUKSI DALAM PENELITIAN HADIS (Analisis Terhadap Kriteria Keabsahan dan Kelemahan Hadis) - As’ad Kholilurrahman; Muhammad Sholihin (Al-Hasyimi - Jurnal Ilmu Hadis, 2024)
The birth and development of hadith are not immune to conflicts of such complexity, leading to the probability that the hadith has been misinterpreted by irresponsible individuals and obscured by power. This is evident in the early days of Islam when hadith was not documented like the Qur'an. Even before the official codification, significant conflicts, such as the intense dispute between Ali and Muawiyah, occurred, giving rise to deviant groups that later fabricated false hadiths to support their factions. Inductive reasoning, as a method of hadith research, serves as a fitting alternative. Even earlier scholars had employed this method, although it was not established as a rigid theory as presented in this writing. Consequently, the inductive method in hadith can aid researchers in identifying elements that may discredit a hadith or, conversely, provide claims regarding the authenticity of a hadith